PREPARING STUDENTS FOR LEADERSHIP: THE ROLE OF UNIVERSITIES - Marshall Christensen (Неперервна професійна освіта: теорія та практика)
The article is devoted to the role of universities in preparing students for leadership. The article states that universities provide opportunities that cultivate the leadership potential of their students, but rarely offer specific guidance for future leaders. The article highlights the experience of Co-Serve International, a non-governmental organization based in the USA, has realized over the past fifteen years in preparing future leaders. The methodology and the principles of CoServe International have been taken by partners to the USA, Kazakhstan, Ukraine, Thailand, Afghanistan, the Philippines and Nigeria. Co-Serve has learned that developing leaders is best achieved by non-traditional teaching methods, such as «action and reflection». Ten Ways Professors Can Model Leadership have been substantiated in the article: an example of leaders in their field of study; cultivatіоn of students self-awareness; respect for personality; a model of teachers’ behaviour as a leadership-service for students; active listening as an act of service; helping students to find their purpose and achieve it; building community as an act of leadership; conflict resolution and development of the skills of forgiveness; creating an atmosphere of trust in the learning community; encouraging students who have achieved certain results.